MEMBENTUK AKHLAK DI ERA REVOLUSI INDUSTRI 4.0 DENGAN PERAN PENDIDIKAN AGAMA ISLAM - Arip Febrianto; Norma Dewi Shalikhah (Elementary School: Jurnal Pendidikan dan Pembelajaran ke-SD-an, 2021)
AbstractAdvances in science and technology entering the millennial era of industrial revolution 4.0 can be enjoyed by mankind. But onthe other hand,  the advancement of science and technology also has a negative impact on many people, especially in today's millennial era   which is very closely related to morality.. Many of the phenomena that occur in society are related to morality. Mislanya case of a student challenging his teacher's fight, the student who is the teacher and there is a case of a student reporting his teacher because of a sepal problem, this is an inappropriate and inappropriate thing to do. The purpose of this research is to find out the role of islamic religious education in shaping morality in the millennial era of the industrial revolution 4.0. The research method uses literature studies by collecting data from documentation using descriptive-analysis methods. Islamic  religious education takes a very important role in addressing  the problem that is happening  at this  time.  In the context of globalization  in the millennial era,education in Indonesia needs to get used to children to understand the existence of the nation in relation to the existence of other nations and all the problems of theworld. Keywords: Morality, Industrial Revolution 4.0,  Islamic Religious Education